2022
DOI: 10.1088/1402-4896/aca99e
|View full text |Cite
|
Sign up to set email alerts
|

Effective role of vacuum annealing in improving structural, optical, and electrical properties of SiO2/Ag/ZnO multilayers deposited by RF sputtering for optoelectronic applications

Abstract: Transparent conductive thin films require multilayer coatings involving metals and dielectrics with high refractive indices. Radiofrequency (RF) magnetron sputtering technique was used to accurately fabricate the SiO2/Ag/ZnO multilayers on the corning glass substrates at 298 K to be used in Concentrating Solar Power (CSP) reflectors, solar cell, and photovoltaic applications. This method optimizes coating processes in a uniform, homogeneous manner, resulting in improved optical and electrical properties, therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…The Tauc formula relates the absorption coefficient (α) of a material to the incident photon energy (hv) through the indirect optical bandgap energy (E g ). The equation is illustrated as follows [33][34][35]:…”
Section: Optical Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tauc formula relates the absorption coefficient (α) of a material to the incident photon energy (hv) through the indirect optical bandgap energy (E g ). The equation is illustrated as follows [33][34][35]:…”
Section: Optical Energiesmentioning
confidence: 99%
“…These functions are especially helpful in disciplines such as semiconductor devices and solid-state physics where the absorption and transfer of energy by electrons play a vital role in device performance and material properties. The real and imaginary components of the dielectric constants are utilized to quantitatively represent the functions of VEL and SEL [33]. These equations are illustrated in figures 14 and 15 can be expressed as follows, as seen in references [46,48]: In the ultraviolet radiation region, it is observed that the VEL and the SEL exhibit a peak, which occurs at the onset of the visible region of the electromagnetic spectrum.…”
Section: Vel and Sel Functionsmentioning
confidence: 99%
“…In fact, when the recombination speed increases, the diode acts like a resistor, hindering the flow and passage of current [32][33][34][35][36]. The integration and interdependence in the properties of chalcogenide compounds, or those that contain at least a chalcogen element, or that are based in their synthesis on silicon and transitional elements, were received extensive studies, as the optical and electrical properties have been employed to determine the suitability of these systems for photovoltaic applications, especially for various uses in solar cells [37][38][39][40][41][42], optoelectronics [43][44][45][46][47][48][49][50][51][52][53][54][55][56], and electrodes [57][58][59][60]. Based on these studies, our current study was a link between the theoretical and experimental parts of the different system compositions of the studied solar cells.…”
Section: (I-v) and (P-v) Data As A Function Of The Solar Irradiance ψmentioning
confidence: 99%